The Multi-Wave Skew-Logistic Process Applied to the UK COVID-19 Pandemic and being Carbon Negative in Climate Change - Cheng, Russell; Williams, Brian (Archives of Clinical and Biomedical Research, 2024)
The Skew-Logistic (SL) function has been proposed to model a reallife dynamic process which rises monotonically to a peak followed by a monotonic falling back. It was introduced to model the first stage of the COVID-19 pandemic in order to forecast its behaviour. Then, with different controls and variants, COVID-19 rose and fell in what might be called a Multi-Wave (MW) behaviour with waves not necessarily the same size. This paper shows how using the Skew Logistic (SL) function for one wave can be modified to model the MW situation. We apply it to two examples. One is to COVID-19 in order to show its more recent behaviour, the other is to climate change, the most serious issue of our time. Some background is provided for both application problems.